2014
DOI: 10.1186/preaccept-1035836021115701
|View full text |Cite
|
Sign up to set email alerts
|

Recombination-mediated escape from primary CD8+ T cells in acute HIV-1 infection

Abstract: Background: A major immune evasion mechanism of HIV-1 is the accumulation of non-synonymous mutations in and around T cell epitopes, resulting in loss of T cell recognition and virus escape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…populations, with only a few single base selection sites, which is typically observed as in our previous analysis of acute/early infection during the first 2 months of infection in adults (Gao et al, 2014;Liu et al, 2013;Ritchie et al, 2014). Thus, our results demonstrate that diversity in these long-term in utero infections was driven by recombination and new mutations mainly accumulated during pregnancy, not after birth.…”
Section: Discussionsupporting
confidence: 81%
“…populations, with only a few single base selection sites, which is typically observed as in our previous analysis of acute/early infection during the first 2 months of infection in adults (Gao et al, 2014;Liu et al, 2013;Ritchie et al, 2014). Thus, our results demonstrate that diversity in these long-term in utero infections was driven by recombination and new mutations mainly accumulated during pregnancy, not after birth.…”
Section: Discussionsupporting
confidence: 81%
“…This rate is within range of that of reported HIV mutation rates (Abram et al, 2010; Ji and Loeb, 1992; Roberts et al, 1988). Recombination has been found to mediate escape from ART (Kellam and Larder, 1995; Moutouh et al, 1996), CD8 + T cells (Ritchie et al, 2014; Streeck et al, 2008), and autologous neutralizing antibodies (Chaillon et al, 2013; Moore et al, 2013; Song et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…RNA recombination is thought to benefit viruses by accelerating combination of beneficial mutations from different lineages (9,10) and/or by purging of deleterious mutations (11,12). Studies in HIV-1 have shown that recombination contributes to the acquisition of multidrug resistance (13,14) and immune escape (15,16), demonstrating the potential advantage of recombination in speeding up production of adaptive genotypes. However, because RNA viruses exhibit high mutation rates and thus may readily generate advantageous combinations by mutation alone, the relative contribution of recombination is unclear.…”
Section: Introductionmentioning
confidence: 99%